1999
DOI: 10.1002/etc.5620180631
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic metal exposure and sediment organic matter on digestive absorption efficiency of cadmium by the deposit‐feeding polychaete Capitella species I

Abstract: Organic matter such as humic acid and bacterial slime exopolymer are common in estuarine and coastal sediments, where they are ingested by animals that process particulate detritus. Both humic acid (HA; refractory) and exopolymer (EPS; easily digestible) bind metals and therefore might represent a source of particulate‐bound metals to deposit‐feeding organisms. This study examined how cadmium preexposure (3 and 30 μg Cd/g dry wt. sed.), gut passage time (GPT), and quality and quantity of the organic coating on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(12 citation statements)
references
References 37 publications
(71 reference statements)
0
8
0
Order By: Relevance
“…Selck et al (9) reported that Cd AE increased with increasing gut passage time in Capitella sp., but this pattern was reversed in worms following preexposure to Cd. Data presented herein suggest that preexposure to elevated Cd or Zn does affect metal AE, in particular, those of Cd following Cd exposure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Selck et al (9) reported that Cd AE increased with increasing gut passage time in Capitella sp., but this pattern was reversed in worms following preexposure to Cd. Data presented herein suggest that preexposure to elevated Cd or Zn does affect metal AE, in particular, those of Cd following Cd exposure.…”
Section: Resultsmentioning
confidence: 99%
“…These studies did not consider metal uptake via the dietary route. Selck et al (9) investigated the effects of chronic metal exposure on the Cd assimilation efficiency by a depositfeeding polychaete Capitella. Cd assimilation efficiency was positively related to gut passage time in unexposed worms, but this pattern was reversed following Cd exposure.…”
Section: Introductionmentioning
confidence: 99%
“…When animals ingest the matrix, coincidentally during their feeding on sediments, cells or flocs, they will consume the sorbed metals and organics as well. EPS have been shown to be an efficient trophic-transfer vehicle for sorbed metals in amphipods (Schlekat et al, 1998, 1999, 2000; Selck et al, 1999), and organic compounds such as pesticides, although most of the latter work has even been conducted in freshwater systems (Widenfalk et al, 2008; Lundqvist et al, 2010, 2012). …”
Section: Animal–microbial Interactions and Food-websmentioning
confidence: 99%
“…Organochlorine pesticides (OCPs) and polychlorinated biphenyls (PCBs) are biologically stable compounds that are hydrophobic and fat-soluble and therefore accumulate in aquatic biota at concentrations that exhibit ecotoxicological effects [2,3]. Moreover, bacterial communities have been shown to bioconcentrate OCPs [4] and extracellular polymeric substances (EPS) that are secreted by the microorganisms in aquatic habitats act as a vector for contaminant uptake into aquatic food webs [5,6]. The increasing usage of these hazardous manmade chemicals has become a matter of great concern.…”
Section: Introductionmentioning
confidence: 99%